Intra-household allocation of time and money - Ko, I (2012)
There are four parts to this thesis: the first chapter analyses the structure of leisure in couples with particular emphasis on joint leisure. We take a structural approach and model the household as a two-stage decision making unit. The findings suggest that couples see joint leisure as a distinct good from private leisure. Specifically when a household decides to have more leisure, almost 40 percent of this increase is allocated to joint leisure as opposed to only 8 to 15 percent allocated to male private leisure. Furthermore, couples prefer to spend leisure together (synchronisation) relative to spending time independently, giving joint leisure the largest weight in the utility function. The findings further suggest that demographics can play a large role in determining the patterns of spousal leisure, with ethnicity and job characteristics being important factors. Finally, when analysing weekend time use patterns, there is evidence to suggest that Saturdays should be distinguished from Sundays as approximately 41 percent more joint leisure is observed on Sundays. The second chapter of the thesis begins our examination of the UK income taxation reform in 1990. The UK went from a system of joint taxation to independent taxation of couples and this reform may have had important implications for households. Across countries, there is a large variation in the income tax treatment of couples. Over the last three decades, many countries have undergone reforms in their tax systems, some have moved from joint to independent taxation, some from independent to joint, while others have begun the practice of allowing couples to choose the system they prefer. This chapter aims to give an overview of the tax treatment of couples and outlines the differences across countries, with particular emphasis on the tax reform in the UK. The third chapter investigates the UK income taxation reform in 1990 and examines how the change from a system of joint to independent taxation of couples has shifted women's relative earning potentials in the household, and how this in turn has led to changes in intra-household assignable clothing expenditures. I apply my method to a sample of UK couples with children and the findings of this chapter show that an exogenous increase in women's income relative to their spouse significantly and substantially increases female clothing expenditure and decreases male clothing expenditure ceteris paribus. However an increase in relative female earnings does not necessarily mean that children will do better relatively. The final outcome may depend on the type of transfer in question. In addition, there is evidence that the final allocations of expenditures on each partner and children may depend significantly on distribution factors such as spousal relative incomes, age gap and educational gap, despite the fact that these variables do not impact on preferences nor on budgets directly. This provides further evidence against the unitary framework in favour of the collective approach and the sharing rule interpretation of how households make decisions in practice. The final chapter of this thesis examines the effects of the tax reform in 1990 with particular emphasis on female labour supply. A method of clarifying the concept of a spouse's individual net income under a joint tax regime is proposed and following the methodology of Blundell et al (2007), the labour supply elasticities for both male and female are estimated. The analysis is extended further to include children in the model and the results show that both the number of children and their age are highly significant for women's labour supply and to a smaller extent also for men. Testing the income pooling hypothesis, the unitary model is not rejected. However, the results strongly reject the hypothesis that distribution factors have no effect on labour supply. The results also suggest that for the group of women affected, the reform generated two opposing effects on their labour supply: a positive effect from an increase in net wage and a negative effect from an increase in bargaining power. On balance, we find that a typical female decreased her labour supply by approximately 2.6 hours per week, yet she still experienced a 22 percent increase in her net income.